2010
DOI: 10.1093/nar/gkq525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pseudouridylation on the structure and activity of the catalytically essential P6.1 hairpin in human telomerase RNA

Abstract: Telomerase extends the 3′-ends of linear chromosomes by adding conserved telomeric DNA repeats and is essential for cell proliferation and genomic stability. Telomerases from all organisms contain a telomerase reverse transcriptase and a telomerase RNA (TER), which together provide the minimal functional elements for catalytic activity in vitro. The RNA component of many functional ribonucleoproteins contains modified nucleotides, including conserved pseudouridines (Ψs) that can have subtle effects on structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 61 publications
13
60
0
2
Order By: Relevance
“…Truncations of CR4/5 RNA showed stem P5 is not necessary for TRBD binding (Fig. S7B, mutants M10-11), in accordance with a previous study that also showed P5 is dispensable for reconstituting telomerase activity in vitro (26). The minimal RNA fragment that retained wild-type binding affinity is only 39 nt, spanning residue 176 to residue 214.…”
Section: Resultssupporting
confidence: 90%
“…Truncations of CR4/5 RNA showed stem P5 is not necessary for TRBD binding (Fig. S7B, mutants M10-11), in accordance with a previous study that also showed P5 is dispensable for reconstituting telomerase activity in vitro (26). The minimal RNA fragment that retained wild-type binding affinity is only 39 nt, spanning residue 176 to residue 214.…”
Section: Resultssupporting
confidence: 90%
“…In addition, a minimal CR4/CR5 domain construct, which includes P6.1, all of P6a-P6b except the terminal hairpin, and flanking nucleotides but does not include the P5 helix, is sufficient to reconstitute telomerase activity in trans with the core domain and TERT (Fig. 5A) (76). Thus, it is not clear whether this region forms a three-way junction in the context of its association with TERT.…”
Section: Ste Of Htrmentioning
confidence: 99%
“…To date, there are no crystal structures of telomerase RNA or telomerase protein-RNA complexes; however, over the last several years, structures of several key hTR elements have been determined by NMR spectroscopy (52,54,55,60,(74)(75)(76). This review summarizes what NMR structural and dynamics studies, combined with biochemical and mutational analysis, have revealed about the functional roles of hTR domains and the overall architecture of hTR.…”
mentioning
confidence: 99%
“…Only the structures of isolated elements have been solved by NMR (Leeper et al 2003;Leeper and Varani 2005;Theimer et al 2005Theimer et al , 2007Chen et al 2006;Richards et al 2006a,b;Kim et al 2008Kim et al , 2010Kim et al , 2014Zhang et al 2010Zhang et al , 2011. Although there have been some previous chemical structure-probing analyses of telomerase RNAs (Antal et al 2002;Forstemann and Lingner 2005), even secondary-structure models have been difficult to validate or refine.…”
Section: Introductionmentioning
confidence: 99%